Incidence and Risk Factors of Obesity in Childhood Solid-Organ Transplant Recipients. Issue 8 (August 2020) - Bondi, Bianca C.; Banh, Tonny M.; Vasilevska-Ristovska, Jovanka; Szpindel, Aliya; Chanchlani, Rahul; Hebert, Diane; Solomon, Melinda; Dipchand, Anne I.; Kim, S. Joseph; Ng, Vicky L.; Parekh, Rulan S.
Abstract : Background: Obesity is a significant public health concern; however, the incidence post solid-organ transplantation is not well reported. Methods: This study determined the incidence and risk factors of obesity among pediatric solid-organ transplant recipients (heart, lung, liver, kidney, multiorgan) at The Hospital for Sick Children (2002–2011), excluding prevalent obesity. Follow-up occurred from transplantation until development of obesity, last follow-up, or end of study. Incidence of obesity was determined overall, by baseline body mass index, and organ group. Risk factors were assessed using Cox proportional-hazards regression. Results: Among 410 (55% male) children, median transplant age was 8.9 (interquartile range [IQR]: 1.0-14.5) years. Median follow-up time was 3.6 (IQR: 1.5-6.4) years. Incidence of obesity was 65.2 (95% confidence interval [CI]: 52.7-80.4) per 1000 person-years. Overweight recipients had a higher incidence, 190.4 (95% CI: 114.8-315.8) per 1000 person-years, than nonoverweight recipients, 56.1 (95% CI: 44.3-71.1). Cumulative incidence of obesity 5-years posttransplant was 24.1%. Kidney relative to heart recipients had the highest risk (3.13 adjusted hazard ratio [aHR]; 95% CI: 1.53-6.40) for obesity. Lung and liver recipients had similar rates to heart recipients. Those with higher baseline body mass index (z-score; 1.72 aHR; 95% CI: 1.39-2.14), overweight status (2.63 HR; 95% CI: 1.71-4.04), and younger transplant age (y; 1.18 aHR; 95% CI: 1.12-1.25) were at highest risk of obesity. Higher cumulative steroid dosage (per 10 mg/kg) was associated with increased risk of obesity after adjustment. Conclusions: Among all transplanted children at The Hospital for Sick Children, 25% developed obesity within 5-years posttransplant. Kidney recipients, younger children, those overweight at transplant, and those with higher cumulative steroid use (per 10 mg/kg) were at greatest risk. Early screening and intervention for obesity are important preventative strategies. Abstract : Supplemental Digital Content is available in the text.